Usual interstitial pneumonia in asbestos‐exposed cohorts – concurrent idiopathic pulmonary fibrosis or atypical asbestosis?. Issue 3 (20th April 2016) - Attanoos, Richard L; Alchami, Fouad S; Pooley, Frederick D; Gibbs, Allen R
Abstract : Aims: To determine whether usual interstitial pneumonia (UIP) pattern fibrosis is seen in asbestosis. Methods and results: The occurrence of UIP pattern fibrosis was studied in four asbestos cohorts systematically referred following postmortem to the UK Pneumoconiosis Unit, Cardiff. The combined exposed workforce comprised >25 000 persons. Over the 17‐year period, 233 subjects were identified; 210 had degrees of interstitial fibrosis with a fibrotic non‐specific interstitial pneumonia pattern and subpleural accentuation, and three showed UIP pattern fibrosis. All three of these cases showed grade 4 fibrosis (honeycombing) with no asbestos fibre dose–response correlation. A Poisson distribution of probability analysis indicated that the observed cases of UIP in this workforce could be wholly accounted for by the prevalence of idiopathic pulmonary fibrosis (IPF) in the population. Conclusions: UIP pattern fibrosis is rarely observed in asbestos‐exposed subjects, and shows no dose–response correlation with asbestos fibres on mineral analysis; this points to an alternative disease, such as IPF. The results indicate that UIP pattern fibrosis should not be regarded as genuine asbestosis, irrespective of the status of asbestos biomarkers, and this impacts upon the postmortem handling of asbestos‐related deaths.